Double Air Chambers Pneumatic Artificial Muscle and Non-Hysteresis Position Control - Naoki Saito; Toshiyuki Satoh; Norihiko Saga (Actuators, 2024)
In this paper, we propose a double air chambers artificial muscle to eliminate the hysteresis in the extension and contraction movement of pneumatic artificial muscles. In this paper, the basic structure of the double air chambers artificial muscle is a rubberless artificial muscle with a particularly large hysteresis loop. The double air chambers artificial muscle aims to eliminate hysteresis by directly pressurizing the inside and outside of the air chamber and actively deforming the air chamber. The hysteresis is reduced by the pressure outside of the air chamber (external pressure). Since the appropriate external pressure varies depending on the contraction force and amount of contraction, we proposed a method to regulate the appropriate external pressure by feedback control. The experimental results show that hysteresis was eliminated in the static characteristics. It was also found that the output gain decreased, and the phase lag increased as the target frequency increased. The output gain did not change with increasing load. The phase lag tended to improve with the PID controller compared to the PI controller. These results suggest that the combination of double air chambers artificial muscle and external pressure-regulated feedback control can achieve non-hysteresis position control, and it is useful as an actuator in mechatronic systems.